Where does the air go? Anatomy and functions of the respiratory tract in the humpback whale (Megaptera novaeangliae) - Reidenberg, Joy S. (Indian Ocean e-Ink, 2018)
Air is a limited resource under water. Pressure changes during diving and ascent further affect buoyancy and sound production/transmission by changing air volumes, densities, and shapes of air spaces and vibration pathways. This paper will focus on how humpback whales use air, and the respiratory tract adaptations that help overcome these challenges. These highly modified respiratory tract tissues function to shunt air to increase oxygenation for extending breath-hold time, conserve and recycle air, maintain hearing at depth, generate sound for communication and navigation, transmit vibrations to water, mitigate noise, support air spaces from collapsing, regulate chamber volumes, produce bubbles as visual signals, control air release as a tool to trap prey, modify center of gravity, regulate buoyancy, and reduce energy expenditure during locomotion. The humpback whale is able to utilize air in an aquatic environment in ways that allow it to support a wide range of unique behaviors. RésuméL’air est une ressource limitée sous l'eau. Les changements de pression au cours de la plongée et de la remontée affectent la flottabilité et la production / transmission des sons en changeant les volumes d'air, les densités et les formes des espaces aériens et des voies de vibration. Cet article se penche sur la façon dont les baleines à bosse utilisent l'air ainsi que les adaptations des voies respiratoires qui participent au processus. Les tissus des voies respiratoires sont hautement modifiés et fonctionnent de manière à shunter l’air pour augmenter l'oxygénation afin de prolonger le temps d'apnée, de conserver et de recycler l'air, de maintenir l'audition en profondeur, de générer des sons pour la communication et la navigation, de transmettre des vibrations à l'eau, d'atténuer le bruit, d’empêcher les espaces devant contenir l'air de s'effondrer, de réguler les volumes des chambres, de produire des bulles servant de signaux visuels, de réguler la libération de l'air qui servira d’outil pour piéger des proies, de modifier ...